The Formation of New Political Science in Modern Russia - E. M. Proshina (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to the necessity of clarifying basic definitions accepted in our modern political science, such as «politics», «culture», «political culture», «civil society», «civic culture»and others. The author argues that this clarification of concepts may be useful in the formation of a new Russian political science, which would take into account specific national features of the past and present development of the country. The present piece is meant to be the first of a series of articles by the same author in whom she intends to further develop the discussion on the object, concepts and methods of Russian political science.